2009
DOI: 10.1111/j.1439-0426.2008.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of six freshwater fishes from small streams flowing into Lake Sapanca, NW Turkey

Abstract: Length-weight relationships are given on six freshwater fish species (Phoxinus phoxinus, Cobitis vardarensis, Neogobius gymnotrachelus, Proterorhinus marmoratus, Petroleuciscus borysthenicus and Gambusia holbrooki) from four streams flowing into Lake Sapanca, north-western Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…There are, however, other biological data available in both ranges, including sex ratios, weight-length (WL) relationships and diet (e.g. Tarkan et al, 2006Tarkan et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, other biological data available in both ranges, including sex ratios, weight-length (WL) relationships and diet (e.g. Tarkan et al, 2006Tarkan et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies on P. semilunaris previously known as Proterorhinus marmoratus [8,26], the b values in the LWRs of P. semilunaris populations in Lakeİznik, Lake Durusu (Terkos Dam Lake) and Lake Sapanca were reported as 3.20, 3.26 and 2.85, respectively. Top et al [11] reported that the estimated values of b inİznik, Sapanca, and Uluabat lake populations were all above 3.0, indicating positive allometry.…”
Section: Discussionmentioning
confidence: 99%
“…Proterorhinus semilunaris is one of the native gobiid species in the fish fauna of Turkish inland waters [1]. Only a few studies have recently been carried out in Turkish part of its native range to fill the gap in knowledge on its bio-ecology, including the length-weight relationship, diel activity, trophic ecology, age structure, somatic growth, and reproductive characteristics of the species [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The LWR and LLRs and condition factors of freshwater fish associated with a number of studies have been carried out previously (Alp and Kara 2004;Bostancı et al 2007;Yılmaz et al 2007;Kırankaya and Ekmekçi 2007;Bostancı et al 2009;Tarkan et al 2009). Nevertheless, there are no adequate studies on growth features of Sakarya bleak.…”
Section: Introductionmentioning
confidence: 99%